Self-Reported Periodization of Nutrition in Elite Female and Male Runners and Race Walkers - Heikura, Ida Aliisa; Stellingwerff, Trent; Burke, Louise Mary (Frontiers in Physiology, 2018)
Athletes should achieve event-specific physiological requirements through careful periodization of training, underpinned by individualized and targeted nutrition strategies. However, evidence of whether, and how, elite endurance athletes periodize nutrition is scarce. Accordingly, elite international female (n=67) and male (n=37) middle/long-distance athletes (IAAF score:1129±54, corresponds to 13:22.49 [males] and 15:17.93 [females] in the 5000m) completed an online survey (February-May 2018) examining self-reported practices of dietary periodization for micro (within/between-days), meso (weeks/months) and macro (across the year) contexts. Data are shown as the percentage of all athletes practicing a given strategy followed by the % of athletes reporting various beliefs or practices within this strategy. Differences according to sex, event (middle-distance [800m/1500m] vs track-distance [3000m-10000m] vs road-distance [marathon/race walks]), caliber (high [major championship qualifier] vs lower), and training volume (low/moderate/high male and female tertiles) were analyzed using Chi-square test or Kruskal-Wallis Test and indicated statistically different when p≤0.05. Most athletes reported eating more on hard training days (92%) and focusing on nutrition before (84%; carbohydrate intake [63%] and timing [58%]) and after (95%; protein goals [59%], timing [55%], carbohydrate goals [50%]) key sessions. Road-distance were the most (62% and 57%), and middle-distance the least (30% and 30%) likely to train fasted (p=0.037) or restrict carbohydrates periodically (p=0.050), respectively. Carbohydrate intake during training (58% of total) was more common in males (79%; p=0.004) and road-distance (90%; p<0.001) than females (53%) or middle/track-distance (48% and 37%). Most athletes (83%) reported following a specific diet before and during race day, with half of the athletes focusing on carbohydrates. Nearly all (97%) road-distance athletes reported following a during-race nutrition plan (carbohydrates/fluids:89%). Only 32% reported taking advice from a dietitian/nutritionist. Based on our analysis: 1) Road-distance athletes periodize carbohydrate availability while track/middle-distance avoid low carbohydrate availability; 2) Middle-distance runners emphasize physique goals to guide their nutrition strategies; 3) Females seem to be more cautious of increasing energy/carbohydrate intake; 4) Among all athletes, nutrition strategies are chosen primarily to improve performance, followed by reasons related to physique, adaptation and health outcomes. Overall, these athletes appear to possess good knowledge of nutrition for supporting training and competition performance.